Barriers to weight management in pregnant mothers with obesity: a qualitative study on mothers with low socioeconomic background - Fahimeh Mehrabi; Najva Ahmaripour; Sara Jalali-Farahani; Parisa Amiri (BMC, 2021)
Abstract Background Maternal obesity is a public health issue that could affect both women's and children's health. This qualitative study aimed to identify barriers to weight management of pregnant women with obesity and low socioeconomic backgrounds. Methods The current qualitative study has been conducted using a grounded theory approach by analyzing data collected from in-depth interviews with clients of Tehran's public health care centers for prenatal care. The criteria for selecting participants were excessive weight gain during the first two trimesters of pregnancy, low socioeconomic status, and willingness to share their experiences. A semi-structured guide consisting of open-ended questions was asked in a private room. Open, axial, and selective coding were applied to the data. Findings Four main themes emerged from data, each of which has some subcategories: 1) personal factors (unpleasant emotions and feelings, personal tastes/hobbies, workload and responsibilities, and history of diseases), 2) pregnancy status (unintended and high-risk pregnancy), 3) interpersonal relationships and support (lack of a spouse's support and unhealthy role modeling of relatives), 4) socio-cultural factors/influences (social norms and values, lack of access to health services, and unreliable information channels). Conclusions This study provides an overview of the barriers to the weight management of pregnant women from low socioeconomic backgrounds. The results could help develop appropriate health strategies for low socioeconomic women with obesity. Also, health care providers for this group of women could use these findings as a guide to consider their conditions and background.